Listening Strategies Employed by the Students at the Tertiary Level in EFL Setting - Asep Hardiyanto (STKIP PGRI Lubuklinggau, 2021)
The objective of this research is to investigate the listening strategies employed by the students at the tertiary level in EFL setting. The current study used descriptive approach which involved six students. They are the representative from the low, medium and high ability students. To achieve the objective of this research, the researchers used interview guideline as the instrument to collect the data. The findings showed that from those six strategies, there were only five strategies which are employed by the students; namely social startegy, cognitive strategy, compensation strategy, metacognitive strategy and affective strategy. From the result of this research, it can be concluded that memory strategy is not employed by the students.